2009
DOI: 10.1074/jbc.m806573200
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 Released from Fibroblasts Is Essential for Up-regulation of Matrix Metalloproteinase-1 Expression by U937 Macrophages in Coculture

Abstract: Matrix metalloproteinases (MMPs) play a key role in periodontal disease. Although it is known that macrophages and fibroblasts are co-localized and express MMPs in the diseased periodontal tissue, the effect of interaction between these two cell types on MMP expression has not been well elucidated. Furthermore although it is known that diabetes is associated with accelerated periodontal tissue destruction, it remains unknown whether hyperglycemia, a major metabolic abnormality in diabetes, regulates MMP expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
66
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 86 publications
(71 citation statements)
references
References 34 publications
4
66
0
1
Order By: Relevance
“…The up-regulation of MMP-1 protein expression followed by inhibition of its activity after exposure to Si/SiO 2 QDs could be explained by the elevated level of TIMP-1 expression, an endogenous inhibitor of this enzyme [53]. Additionally, the release of IL-6 might be responsible for the upregulation of MMP-1 expression as reported previously [54]. These changes in MMPs expression and activity were similar to the molecular events involved in the pathogenesis of chronic rhino-sinusitis without nasal polyps, which involves high levels of IL-6 and IL-8 that trigger fibrosis by up-regulating TIMP-1 in fibroblasts [55].…”
mentioning
confidence: 62%
“…The up-regulation of MMP-1 protein expression followed by inhibition of its activity after exposure to Si/SiO 2 QDs could be explained by the elevated level of TIMP-1 expression, an endogenous inhibitor of this enzyme [53]. Additionally, the release of IL-6 might be responsible for the upregulation of MMP-1 expression as reported previously [54]. These changes in MMPs expression and activity were similar to the molecular events involved in the pathogenesis of chronic rhino-sinusitis without nasal polyps, which involves high levels of IL-6 and IL-8 that trigger fibrosis by up-regulating TIMP-1 in fibroblasts [55].…”
mentioning
confidence: 62%
“…The medium was changed every 2–3 days. Our previous studies have shown the similarity between U937 cells and human monocytes in cellular response to LPS (Samuvel et al; Sundararaj et al, 2008; Sundararaj et al, 2009). For cell treatment, LPS from E. coli (Ec) (Sigma, St. Louis, MO) and pam2CSK4 and pam3CSK4 (InvivoGen, San Diego, CA) were used.…”
Section: Methodsmentioning
confidence: 87%
“…Carlsbad, CA) containing normal glucose (5 mM) or high glucose (25 mM), 10% fetal calf serum, 1% MEM non-essential amino acid solution, and 0.6 g/100 ml of HEPES. Five and 25 mM of glucose have been used commonly as the concentrations of normal and high glucose, respectively (Nareika et al, 2008, Nareika et al, 2007, Sundararaj et al, 2009). …”
Section: Methodsmentioning
confidence: 99%